Plagiarism- A Scientific Misconduct (Advancements in Homeopathic Research, 2022)
Plagiarism is referred to as literary copying or  stealing work or idea without acknowledgment of an  original author that ultimately hampers the quality of  an article. Plagiarism is rampant in current times as  writers donot have knowledge about this unethical  malpractice. Also, with easily available information  on any topic through internet, writers indulge in the  wrong trend of copying to prepare their articles with  greed to gain name, fame and also increase the number  of their publications for promotions and salary hike. The writers indulging in plagiarism are considered  incompetent and these dishonest perpetrators have to  face punishments and they even lose their reputation. This review article deals with historical background,  causes, types of plagiarism; role of publication  agencies, plagiarism detection tools and strategies to  avoid it. The need of the hour is to create awareness  as to what constitutes plagiarism by conducting  seminars, workshops on guidelines that need to  be followed by the authors while writing articles.  Maximum responsibility lies with the authors to  follow the moral, honest policies and not to indulge  in fraudulent behavior.
Keywords: Ethics; Literary theft; Plagiarism; Plagiarism detection tools; Publication agencies; Punishment